Cataloguing - Hunter, Eric J.; Bakewell, K. G. B. (London : Library Association Pub., 1991)
A comprehensive exposition of cataloguing and indexing. It has been updated to take account of the many significant developments in the field over the recent years.
Includes bibliographical references and index.
oif 29/01/15
Loan
Keywords: Cataloging; Descriptive cataloguing; Library science